ENHANCING SPEAKING SKILLS FOR B2 LEVEL LEARNERS - Jabborova Shoira; Asqarov Sherbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article studies the analysis of the similar versions of the idioms expressed by human body parts in the English language, which are actively used in conversation today, and the considerations aimed at their classification, and their replacement with the Uzbek alternative. In the article, the idioms given in both languages ​​are used in sentences and their meaning is analyzed.